2018
DOI: 10.1002/term.2788
|View full text |Cite
|
Sign up to set email alerts
|

Porcine‐Derived Biomaterials in Tissue Engineering and Reconstructive Surgery: Considerations and Alternatives in Muslim Patients

Abstract: During the last three decades, tissue engineering and reconstructive surgery have become standard therapeutic options in the world of medicine. Several biomaterials, either alone or in combination with cultured cellular products, have been introduced to compensate for the scarcity of autologous donor tissue or to improve healing in a variety of surgical specialties, for example, abdominal/visceral surgery, plastic surgery, and cardiovascular surgery. Many of these biomaterials are of porcine origin.It is well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Although porcine-derived collagen membranes have become the new gold standard as resorbable barrier membranes for GBR, recent results have shown that bovine-sourced materials seem to provide a special integration pattern including a so-called "secondary porosity" in combination with a transmembraneous vascularization pattern that can potentially serve as a further basis to support the restitutio ad integrum of jawbone defects [39,40]. Thus, such a barrier membrane may bioactively contribute to the osseous regeneration via generation of a healing-supportive microenvironment during the GBR proce- At day 90 post implantationem, comparable mean vessel diameter values were detected in all study groups (Figure 18 and Table 11).…”
Section: Discussionmentioning
confidence: 99%
“…Although porcine-derived collagen membranes have become the new gold standard as resorbable barrier membranes for GBR, recent results have shown that bovine-sourced materials seem to provide a special integration pattern including a so-called "secondary porosity" in combination with a transmembraneous vascularization pattern that can potentially serve as a further basis to support the restitutio ad integrum of jawbone defects [39,40]. Thus, such a barrier membrane may bioactively contribute to the osseous regeneration via generation of a healing-supportive microenvironment during the GBR proce- At day 90 post implantationem, comparable mean vessel diameter values were detected in all study groups (Figure 18 and Table 11).…”
Section: Discussionmentioning
confidence: 99%
“…ADM is fabricated by the removal of cellular components from the dermal compartment, exhibiting natural bioactive signals, suitable compatibility with living tissues, and mechanical characteristics, which thus functions as a structural scaffold consisting of extracellular matrix components ( Nikolova and Chavali, 2019 ; Dussoyer et al, 2020 ). Based on its derivation, current ADMs that exist commercially are categorized into human-derived ADMs, porcine-derived ADMs, and bovine-derived ADMs ( Almarzouqi et al, 2018 ; Pires et al, 2022 ). In this study, we investigated the histological and biochemical characteristics of the novel human-derived ADMs (scADM) produced by DOF company in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Because most collagen is derived from animals such as bovines and pigs, its use is expected to be difficult for religious reasons. For example, it is well known that Islam, which accounts for 23% of the world's population (1.6 billion people), prohibits the consumption of pork and its products [32]. CA bone graft material does not contain collagen complexes and is therefore considered to be a viable bone graft material for use in many countries.…”
Section: Discussionmentioning
confidence: 99%